2014
DOI: 10.1155/2014/562860
|View full text |Cite
|
Sign up to set email alerts
|

Multimarker Screening of Oxidative Stress in Aging

Abstract: Aging is a complex process of organism decline in physiological functions. There is no clear theory explaining this phenomenon, but the most accepted one is the oxidative stress theory of aging. Biomarkers of oxidative stress, substances, which are formed during oxidative damage of phospholipids, proteins, and nucleic acids, are present in body fluids of diseased people as well as the healthy ones (in a physiological concentration). 8-iso prostaglandin F2α is the most prominent biomarker of phospholipid oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 119 publications
(111 reference statements)
2
63
0
Order By: Relevance
“…This interpretation is consistent with the current understanding that extra pulmonary translocation of poorly soluble nanoparticles (including nanoTiO 2 ) is low (typically <0.1%), and the vast majority of circulating nanoparticles accumulate in the liver. However, urine has repeatedly been shown to be a sensitive medium for monitoring systemic changes in other exposure scenarios (Syslova et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interpretation is consistent with the current understanding that extra pulmonary translocation of poorly soluble nanoparticles (including nanoTiO 2 ) is low (typically <0.1%), and the vast majority of circulating nanoparticles accumulate in the liver. However, urine has repeatedly been shown to be a sensitive medium for monitoring systemic changes in other exposure scenarios (Syslova et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…8-Isoprostane causes vasoconstriction of blood vessels and bronchi, lowers blood flow in the kidneys, and participates in the pathology of several diseases, such as lung diseases, atherosclerosis, and diabetes (Czerska et al, 2016;Syslova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ROS/RNS formation and oxidative stress carcinogenesis is associated with several chronic oxidative conditions, including inflammation, infection and exposure to asbestos or silica 33 34 35. High concentrations of 8-OHG and 8-OHdG were determined not only in the body fluids or lung tissues in subjects with chronic obstructive pulmonary disease and high air pollution exposure, but also in connection with age-related and/or degenerative diseases, such as type II diabetes, hypertension and several types of cancer 36. For example, 5-OHMeU has been used as a marker of cardiovascular diseases 37.…”
Section: Discussionmentioning
confidence: 99%
“…8-iso prostaglandin F 2α is a biomarker for phospholipid damage. 8-hydroxy-2′-deoxyguanosine and 8-hydroxyguanosine are produced by the oxidative damage of nucleic acids 69 . The concentration of these biomarkers in body fluids can be detected via high-performance liquid chromatography and mass spectrometry.…”
Section: Molecular Biomarkers Of Agingmentioning
confidence: 99%